2009
DOI: 10.1161/circulationaha.108.820720
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Properties of Myocardial Bridge Predisposing to Myocardial Infarction

Abstract: Background-A myocardial bridge (MB) that partially covers the course of the left anterior descending coronary artery (LAD) sometimes causes myocardial ischemia, primarily because of hemodynamic deterioration, but without atherosclerosis. However, the mechanism of occurrence of myocardial infarction (MI) as a result of an MB in patients with spontaneously developing atherosclerosis is unclear. Methods and Results-One hundred consecutive autopsied MI hearts either with MBs [MI(ϩ)MB(ϩ) group; nϭ46] orwithout MBs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
2
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 30 publications
4
142
2
13
Order By: Relevance
“…Several studies using CAG, CTCA and IVUS have demonstrated that myocardial bridging of the LAD is often associated with atherosclerotic lesions proximal to the bridge whereas the tunnelled segment and the distal portion are conspicuously free from atherosclerosis [9,15,31,33,34] (Fig. 3).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using CAG, CTCA and IVUS have demonstrated that myocardial bridging of the LAD is often associated with atherosclerotic lesions proximal to the bridge whereas the tunnelled segment and the distal portion are conspicuously free from atherosclerosis [9,15,31,33,34] (Fig. 3).…”
Section: Pathophysiologymentioning
confidence: 99%
“…3). Factors that may play a role in causing the atherosclerotic lesions include flow disturbances (such as retrograde flow during systole), pressure disturbances that may cause endothelial injury, high wall stress proximal to the bridge and tensile stress; conversely development of atherosclerosis may be prevented in the tunnelled and distal segments by inhibition of coronary artery wall motion of the tunnelled segment and lower pressures [5,19,31,34,35].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Inflammatory mediators such asadiponectin and adrenomedullin seem to play a protective effect, while the pro-inflammatory mediator such as interleukins1and 6 (IL-1, IL-6) and tumor necrosis factor alpha (TNF-á) supposedly exert detrimental effect [12] (Figure 3). variations of the myocardial bridges with a predisposition to the risk of cardiac ischemia is still a detail to be clarified [10,11].…”
Section: Paracrine Signaling Of Epicardial Adipose Tissuementioning
confidence: 99%
“…MB, genellikle asemptomatik bir anomali olmasına rağmen miyokardiyal iskemi ve infarktüs, ileti anomalileri, ventriküler aritmi ve ani ölüm görülebilmektedir (10,(21)(22)(23)(24)(25)(26)(27). İntravasküler ultrasonografi ve intrakoroner doppler gibi tekniklerin gelişmesi, iskemi mekanizmasının daha iyi anlaşılmasına katkıda bulunmaktadır (28). MB'de kan akımının engellenmesi sistol sırasında oluştuğu saptanmıştır (10).…”
Section: Introductionunclassified
“…Yapılan çalışmalarda sistolik koroner kan akımındaki bozulmaya ilaveten diyastolik koroner kan akımının da bozulduğu tespit edilmiştir (10,29). MB olan segmentin uzunluğu, kalınlığı, lokalizasyonu, taşikardi, hipotansiyon ve artmış platelet agregasyonu MB'li hastalarda semptom oluşmasına etkili olan anatomik ve fizyolojik mekanizmalardır (28). MB içinde kalan segmentin uzunluğu iskemi oluşturmada oldukça önemlidir (30).…”
Section: Introductionunclassified